ADEQUAÇÃO DE PROPRIEADES DE AGRICULTORES FAMILIARES À LEGISLAÇÃO AMBIENTAL: A EDUCAÇÃO AMBIENTAL COMO MITIGADORA DO PROCESSO - Klein, Marcelo André; Rosa, Marcelo Barcellos da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
The environmental suitability of the property with the environmental legislation is a legalrequirement today. The present work has as main objective to use environmental education as atool to the process of adjusting the properties of the Family Agriculture of Rio Grande do Sul Stateto environmental legislation. In Rio Grande do Sul State, the majority of the properties areclassified as Family Farming. It’s main features are the small size of areas for exploration andcrops, intensive land use, large production of income and use of hand labor per unit area and is aproducer of staple foods consumed by the population. In terms of legislation, the Forestry Code isthe principal law package acting on the properties of Family Farming. The Forest Code stipulatesthe main forms of environmental preservation of the Permanent Preservation Areas and LegalReserves. These conservation areas have many functions for both the property and to society. Theproducer must comply with the dimensions imposed for these areas. To do so takes many forms such as netting, natural regeneration and, for example, restoration to the legal reserve and naturalregeneration, planting native species and planting native species combined with naturalregeneration. Agroforestry can be a solution in the restoration/remediation for PermanentPreservation Areas and Legal Reserves. Environmental education act as a catalyst in theseprocesses leading information. Therefore, the family farmer can adapt itself and understand howthey can cause or remedy the least possible damage to their production systems.